The Ag-Au Pallancata mine : a low-sulphidation epithermal system in southern Peru - Gutierrez, Neper Klein Condori (2016)
The Ag-rich Pallancata epithermal district is located in the Huaylilllas magmatic arc along the Neogene belt of southern Peru, which historically produced more than 58 Moz of Ag. The mineralization occurs in quartz veins hosted by 16.58±016 Ma dacitic ignimbrites. Ore minerals include proustite-pirargirite, polibasite-pearceite and argentite with sphalerite, galena and chalcopyrite to a lesser extent; quartz, pyrite, adularia and sericite represent the main gangue minerals. Hydrothermal alteration evolved from regional propylitic to proximal quartz-illite+pyrite and quartz-adularia+pyrite±illite. The mineralized veins fill open spaces in NW-trending, high-angle, subparallel, transtensional faults with sinistral movement and in related extension fractures. Veins are 1 to 30 m wide and up to 3 Km in length with a recognized depth of 350 m. The Pallancata evolution is complex and multiepidsodic and recorded by gangue mineral textures, which include crustiform-, colloform-, cockade- and comb-textured quartz, rhombic adularia and bladed calcite replaced by quartz; the latter two suggests boiling as a precipitation mechanism. The vein evolution records seven stages of gangue and ore deposition with the main mineralization event related to the stage 5, the bonanza stage. The fluid inclusion petrography and microthermometry in quartz from bonanza stage revealed FIA’s mostly consisting of biphasic inclusions (LH2O-VH2O). Homogenization temperatures (Th) and calculated salinities are low with a mean, respectively, around 1.77 % NaCl eq. and 207°C. Raman spectroscopic studies showed SO2 as a minor additional vapor phase and confirmed the lack of CO2. Oxygen isotopes ratios in quartz and adularia and the resulting mean isotopic δ18O composition for water in equilibrium with both minerals is around -7.0 ‰ suggesting a meteoric source for the mineralizing fluid. All the above presented characteristics suggests the Pallancata mineralization as a low-sulphidation epithermal system.